Effect of using L_arginine in reducing the heart toxicity produced from use Doxorubicin anticancer drug on some hormones in the experimental male rabbits - Abeer Talib A. H; Zaid M. Mubark AL-Mahdawi; Saleh M. Rahim AL-Obaidy (Tikrit Journal of Pure Science)
This study amid to search the role of L_arginine in reducing the heart toxicity and atherosclerosis which result from using of  Doxorubicin in treatment of cancer Also the role of hydrogen peroxide in inducing oxidative stress in Laboratory Albino rabbit as Growth Hormone and (T3,T4,TSH) levels, the  Study included 40 male rabbits, where each group consist of 5 animals The results showed a high Significant decrease in Growth Hormone concentration (P≤0.01) in Dox group (15mg/kg of.w) and group of animals treated with H2O2 alone while the concentrations of  GH  had been increase with high significant (P≤0.01) in other groups. The results showed a high significant (P ≤ 0.01) in the hormone T4  concentration in serum in the group H2O2 and Dox group alone compare with control and the occurrence of a highly significant increase (P≤0.01)of Hormone T3,T4 concentrations in Animal group treated with Dox (15 mg/kg) and  L-arginine Also group treated with H2O2 and L-arginine, and group treated with Cholesterol and L-arginine. while high significant decrease (P≤0.01) had been happened in Hormone (T3) (T4) concentration in sera of other groups of animals compared with the control. and found through the study and having High Significant decrease in TSH concentration (P≤0.01) in serum in the group treated with Dox and L-arginine, and group treated with Cholesterol and L-arginine compared with the control .there were no significant differences in the concentration of  the hormone TSH in the group H2O2 alone while the concentrations of TSH had been increase with high significant (P≤0.01) in other groups.